The Aesthetics of Authenticity: Medial Constructions of the Real - Groß, Florian; Huber, Irmtraud; Funk, Wolfgang (transcript, 2014)
As a concept that increasingly gains importance in contemporary cultural discourse, authenticity emerges as a site of tearing tensions between the fictional and the real, original and fake, margin and centre, the same and the other.The essays collected in this volume explore this paradoxical nature of authenticity in the context of various media. They give ample proof of the fact that authenticity, which depends on giving the impression of being inherent or natural, found not created, frequently turns out to be the result of a careful aesthetic construction that depends on the use of identifiable techniques with the aim of achieving certain effects for certain reasons.